Colloid transport in saturated porous media: Elimination of attachment efficiency in a new colloid transport model. Issue 5 (30th May 2013) - Landkamer, Lee L.; Harvey, Ronald W.; Scheibe, Timothy D.; Ryan, Joseph N.
Key Points This colloid transport model eliminates the empirical attachment efficiency. Introduce a new paradigm for colloid re‐entrainment behavior. Model parameters related to magnitude of secondary energy minimum